STRATEGIC IMPERATIVES ENSURING POPULATION WELFARE UNDER TRANSFORMATION EXCLUSION CONDITIONS - Druzhynina, Viktoriia; Likhonosova, Ganna (Baltic Journal of Economic Studies, 2017)
The purpose of the research is to substantiate strategic imperatives that should be taken into account in developing algorithms for improving the welfare of the population in the conditions of socio-economic transformation and the emergence of exclusion impulses. The subject of the research is the theoretical and applied aspects of the development of strategic imperatives for the transformation of socio-economic relations in different regions of Ukraine. The methodology of the research is based on methods of correlation-regression analysis – to assess the standard of living of the population, taking into account regional specifics; logical-heuristic, economic-mathematical analysis – to identify the relationship between the needs of the population of different regions and their priority; spatial vector modelling – to predict the level of average wages of the population; as well as for diagnosing the welfare of the population, taking into account the influence of factors of socio-economic transformation and emerging rejection; inverse method – the adequacy of the obtained models and forecasts with the help of verification of predictive values is checked. Results. The research confirmed that the effectiveness of achieving the welfare of the population depends on the degree of restrictions within the framework of socio-economic transformations, the emergence of impulses of social and economic exclusion. The authors developed an algorithm for estimating and modelling the living standards of the urban population. The implementation of the algorithm occurs by: determining the result indicator of the living standards of the population of the city to select the priority factors of influence on the result indicator; detection of the dependence between the result indicator and the factors of influence; the choice of the optimal predictive function for the forecast of the development of the main components (factors) of the result indicator; forecast of the level of the result indicator. At the stages of implementation of the algorithm, a multivariate econometric model for forecasting the living standards of the urban population is constructed. The model proposed by the author is adequate, its statistical quality, significance, and reliability are sufficient for use in forecasting socio-economic processes of city development. The practical significance of the study is to provide methodological and applied tools for finding compromise solutions to neutralize the negative effects of socioeconomic rejection and to promote the welfare of the population in different regions of Ukraine, which unites the entire Ukrainian nation to address the priority tasks that provide the maximum socio-economic effect. Value/originality. The conducted research allowed confirming the obtained results: the implementation of a phased algorithm for forecasting the standard of living of the population depends on a set of strategic and alternative transformational decisions; prolongation of studies of processes of socioeconomic transformation and emerging rejection is ensured by the influence of factors of increasing or decreasing welfare of the population; the level of wages, as an indicator of the quality of life of the population, contributes to the formation of a strategy for improving the welfare of the population. Such a complex of actions aimed at solving the problems of finding alternative solutions, adopting, implementing and monitoring the concerted actions of the population and governmental organizations will strategically ensure the achievement of high quality and standard of living of people, giving them the opportunity to realize their own development goals.